Mobile application-based media learning and its’ effect on students’ learning motivation - Fajar Indra Kusuma; Nunuk Suryani; Sri Sumaryati (International Journal of Evaluation and Research in Education (IJERE), 2022)
Online learning is a solution used during the COVID 19 pandemic. This study aimed to determine the conditions of learning during the pandemic and the development of mobile application-based learning media. This was a research and development (R&D) in the context of developing mobile application-based learning media. The results of the development of learning media by researchers indicate that experts and students have positive opinions about this cellular application-based learning media. All experts from media experts, materials experts and expert practitioners stated that this media is "very worthy". The results of the perception questionnaire of 126 respondents also rated this media "very worthy" with a percentage value of 86.30%. In addition, the post-test revealed that learning media based on mobile applications is proven to be effective in increasing students' learning motivation.